2019
DOI: 10.9744/jmk.21.1.41-50
|View full text |Cite
|
Sign up to set email alerts
|

Apology and Compensation Strategy on Customer Forgiveness and Negative Word of Mouth

Abstract: The service provider could not totally guarantee the service process without any failure at all. This study aims to measure the influence of service recovery strategy towards customer forgiveness and negative word-of-mouth (WOM) as the effect of service failure. The service recovery strategy is performed in three types of vignette: apology, compensation, and apology-compensation. Vignette was given to 94 participants who have encountered service of airline. The result of ANOVA shows that apology compensation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 33 publications
(44 reference statements)
0
3
0
Order By: Relevance
“…Negative emotions are triggered by service failures, which have an impact on customer satisfaction towards service providers. According to Bakar, Hidayati, & Giffani (2019), service failures are overcome by providing recovery strategies such as compensation, apologies, and a responsive attitude. Post-recovery emotions minimize the negative impacts due to service errors, thereby, leading to positive customer evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Negative emotions are triggered by service failures, which have an impact on customer satisfaction towards service providers. According to Bakar, Hidayati, & Giffani (2019), service failures are overcome by providing recovery strategies such as compensation, apologies, and a responsive attitude. Post-recovery emotions minimize the negative impacts due to service errors, thereby, leading to positive customer evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…attitudes. Therefore, companies should monitor and manage word-of-mouth to ensure positive perceptions of their products or services [26,27].…”
Section: Methodsmentioning
confidence: 99%
“…Negative word-of-mouth can be damaging as it spreads quickly and may result in decreased consumption and brand attitudes. Therefore, companies should monitor and manage word-of-mouth to ensure positive perceptions of their products or services [ 26 , 27 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Due to the service failure a customer may act in three different actions i.e publicly act, private action or forgive means no action so publicly act means a customer involve any legal party or institution, private action referred as a customer have no desire to stay with the service provider and will spread negative word of the mouth whereas the no action means a customer forgive the service provider and will not willing to do ant action against the service provider (Bakar et al, 2019;Sengupta et al, 2024).…”
Section: Service Failure Severitymentioning
confidence: 99%
“…Gronroos suggested that service providers take some action after service failure as consumer's expectation related to the services does not match the delivered (Grönroos, 2007;Harrison-Walker, 2019a).The paradox of service recovery has importance with the condition that the customer becomes more satisfied after service recovery than those who have not such failure experience (Soares & Proença, 2015;Yunus, 2023).Previous studies suggested that after service failure, customers have feelings of injustice and they expect to restore the feelings of justice (Suri et al, 2019). The service failure which may cause cost or material damage to the customer might increase the need for recovery strategies like empathy and continuous concern whereas for the customer who responds to emotions like anger immediate correction and apologies recovery strategies can be adopted (Bakar et al, 2019). Kenny (1988) identified the recovery strategies into two types i.e Physical and psychological recovery strategy and Smith et al (1999) review these and suggested two categories of compensation that are physical compensation and psychological compensation (Tsai et al, 2014;Wang et al, 2023).…”
Section: Service Recovery Strategiesmentioning
confidence: 99%